The Difference Plasma Levels of Endotelin-1 in Type 2 Diabetes Mellitus Women with and without Hypertension - Enita Rahmawati Kurniatmaja; Hemi Sinorita; Lutfan Budi Purnomo (Faculty of Medicine Universitas Gadjah Mada, 2015)
Background. Diabetes and hypertension are related to each other and have a strong pre-disposition on the incidence of atherosclerosis. The incidence of hypertension 2 times greater in patients with DM than non DM. Endothelial dysfunction underlies these events. Endothelial markers, endothelin-1 is known to affect blood pressure.Aim. The aim of this study is to determine the difference plasma levels of endothelin-1 in type 2 diabetes mellitus in women with and without hypertension.Methods. The cross sectional design was conducted on women with type 2 diabetes mellitus with and without hypertension at metabolic and endocrinology clinic, Dr. Sardjito General Hospital Yogyakarta from July 2010 until the sample met the criterias. Subjects were divided into two groups, type 2 DM woman with hypertension groups and without hypertension. ELISA sandwich’s method was used to measure plasma levels of endothelin-1. Characteristics of the study are presented in the form of mean Kurniaatmaja et al.Results. In this research, the plasma levels of endothelin-1 in in type 2 diabetes mellitus in women with hypertension (n=32) and without hypertension (n=32) respectively 19.17±7.53 ng/ml and 13.75±6.19 ng/dl, and this difference was stastistically signifi cant with p= 0.003 CI 95% -8.87 to -1.97.Conclusion. Plasma levels of endothelin-1 in type 2 diabetes woman with hypertension higher than without hypertension.